Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Lead-time-dependent calibration of a flood forecasting model - Paul C. Astagneau; François Bourgin; Vazken Andréassian; Charles Perrin (Journal of Hydrology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Climate change vulnerability of Arctic char across Scandinavia - Clint C. Muhlfeld; Timothy J. Cline; Anders G. Finstad; Dag O. Hessen; Sam Perrin; Jens Thaulow; Diane Whited; Leif Asbjørn Vøllestad (Global Change Biology, 2024)
Climate change is anticipated to cause species to shift their ranges upward and poleward, yet space for tracking suitable habitat conditions may be limited for range‐restricted species at the highest elevations and latitudes of the globe. Consequently, range‐restricted species inhabiting Arctic freshwater ecosystems, where global warming is most pronounced, face the challenge of coping with changing abiotic and biotic conditions or risk extinction. Here, we use an extensive fish community and environmental dataset for 1762 lakes sampled across Scandinavia (mid‐1990s) to evaluate the climate vulnerability of Arctic char ( Salvelinus alpinus ), the world's most cold‐adapted and northernly distributed freshwater fish. Machine learning models show that abiotic and biotic factors strongly predict the occurrence of Arctic char across the region with an overall accuracy of 89 percent. Arctic char is less likely to occur in lakes with warm summer temperatures, high dissolved organic carbon levels (i.e., browning), and presence of northern pike ( Esox lucius ). Importantly, climate warming impacts are moderated by habitat (i.e., lake area) and amplified by the presence of competitors and/or predators (i.e., northern pike). Climate warming projections under the RCP8.5 emission scenario indicate that 81% of extant populations are at high risk of extirpation by 2080. Highly vulnerable populations occur across their range, particularly near the southern range limit and at lower elevations, with potential refugia found in some mountainous and coastal regions. Our findings highlight that range shifts may give way to range contractions for this cold‐water specialist, indicating the need for pro‐active conservation and mitigation efforts to avoid the loss of Arctic freshwater biodiversity.

Possibly seismically triggered avalanches after the S1222a Marsquake and S1000a impact event - A. Lucas; I.J. Daubar; M. Le Teuff; C. Perrin; T. Kawamura; L. Posiolova; P. Lognonné; S. Rodriguez; D. Giardini; G. Sainton; A. Mangeney; A. McEwen (Icarus, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Challenges and opportunities in the use of ponds and pondscapes as Nature-based Solutions - M. Cuenca-Cambronero; M. Blicharska; J.-A. Perrin; T. A. Davidson; B. Oertli; M. Lago; M. Beklioglu; M. Meerhoff; M. Arim; J. Teixeira; L. De Meester; J. Biggs; et al. (Hydrobiologia, 2023)
Ponds and “pondscapes” (networks of ponds) are crucial habitats for biodiversity and for delivering multiple benefits to humans, so-called “Nature’s Contribution to People”, such as climate mitigation and adaptation to climate change, creation, and maintenance of habitat for biodiversity, water purification, flood mitigation and cultural benefits (e.g., recreational possibilities). However, ponds are not often considered as Nature-based Solutions to provide all these benefits. In addition, there is insufficient knowledge on how to manage and restore ponds to maximise their role to increase the resilience of ecosystems and society to climate change. To facilitate improved implementation of ponds as Nature-based Solutions for the delivery of a wide range of Nature Contributions to People, it is important to generate and integrate biodiversity, ecosystems, societal, economic and policy knowledge. Hence, there is a need for evidence-based guidance to support the broader use of ponds. Here, we review the role of ponds and pondscapes in delivering Nature’s Contributions to People and provide an overview of the challenges and opportunities for their broader implementation as Nature-based Solutions. Finally, we propose a conceptual framework that can help the implementation of pond Nature-based Solutions, and that outlines future research needs.

Structure-based optimization of aminothiadiazole inhibitors of AKT - Deborah S. Mortensen; Sayee G. Hegde; Sophie M. Perrin-Ninkovic; Sogole Bahmanyar; Meg McCarrick; Roy Harris; Robert Hilgraf; Branden G. S. Lee; Jeff McKie; Lisa Nadolny; John Sapienza; Alice Collette; et al. (Medicinal Chemistry Research, 2023)

4500 years of morphological diversification in Western Europe wild boars (Sus scrofa) and the consequences of the Neolithic transition - T. Cucchi; H. Harbers; D. Neaux; M. Balasse; L. Garbé; D. Fiorillo; H. Bocherens; D. Drucker; C. Zanolli; R. Cornette; R.M. Arbogast; S. Bréhard; et al. (Quaternary Science Reviews, 2023)

When does a parsimonious model fail to simulate floods? Learning from the seasonality of model bias - Paul C. Astagneau; François Bourgin; Vazken Andréassian; Charles Perrin (Hydrological Sciences Journal, 2021)

Effects of a multifaceted intervention to promote the use of intravenous iron sucrose complex instead of ferric carboxymaltose in patients admitted for more than 24 h - Justine Touchard; G. Perrin; S. Berdot; J. Pouchot; M. C. Loustalot; B. Sabatier (European Journal of Clinical Pharmacology, 2021)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Guidelines and quantitative standards to improve consistency in cetacean subspecies and species delimitation relying on molecular genetic data - Barbara L. Taylor; Frederick I. Archer; Karen K. Martien; Patricia E. Rosel; Brittany L. Hancock‐Hanser; Aimee R. Lang; Matthew S. Leslie; Sarah L. Mesnick; Phillip A. Morin; Victoria L. Pease; William F. Perrin; Kelly M. Robertson; et al. (Marine Mammal Science, 2017)
Taxonomy is an imprecise science that delimits the evolutionary continuum into discrete categories. For marine mammals, this science is complicated by the relative lack of morphological data for taxa that inhabit remote and often vast ranges. We provide guidelines to promote consistency in studies relying primarily on molecular genetic data to delimit cetacean subspecies from both populations and species. These guidelines identify informational needs: basis for the taxonomic hypothesis being tested, description of current taxonomy, description of relevant life history, sample distribution, sample size, number and sequence length of genetic markers, description of measures taken to ensure data quality, summary statistics for the genetic markers, and analytical methods used to evaluate the genetic data. We propose an initial set of quantitative and qualitative standards based on the types of data and analytical methods most readily available at present. These standards are not expected to be rigidly applied. Rather, they are meant to encourage taxonomic arguments that are consistent and transparent. We hope professional societies, such as the Society for Marine Mammalogy, will adopt quantitative standards that evolve as new data types and analytical methods become widely available.

Why we should develop guidelines and quantitative standards for using genetic data to delimit subspecies for data‐poor organisms like cetaceans - Barbara L. Taylor; William F. Perrin; Randall R. Reeves; Patricia E. Rosel; John Y. Wang; Frank Cipriano; C. Scott Baker; Robert L. Brownell (Marine Mammal Science, 2017)
Obtaining the representative morphological data required for traditional taxonomy is difficult, and sometimes impossible, for cetaceans, especially large ones. As a result, three quarters of the 88 currently recognized extant species have no subspecies and 40 taxa likely have additional unnamed taxa. Conservation needs give urgency to improving taxonomy because unnamed taxa are unlikely to receive protection equivalent to that received by named taxa. Genetic data can improve efforts to delimit subspecies, but the markers and methods used have varied and the magnitude of genetic difference used to justify subspecies distinctions across studies has also varied. Here, we define the concepts of populations, subspecies, and species to establish a foundation for developing guidelines (data to include and analyses to conduct) and quantitative standards (the magnitude of differentiation expected at different taxonomic levels) for using genetic data to support taxonomic recognition. Our definition is particularly applicable to data‐poor groups because it allows for naming a subspecies when there is uncertainty about whether lineages have diverged sufficiently for species‐level recognition. This allows a species that lacks convincing data for lineage divergence to be recognized as a subspecies while sufficient data are accrued, which could take decades for some cetaceans.

Visuo-oculomotor skills related to the visual demands of sporting environments - Hadrien Ceyte; Alexis Lion; Sébastien Caudron; Philippe Perrin; Gérome C. Gauchard (Experimental Brain Research, 2017)

Investigation of recharge dynamics and flow paths in a fractured crystalline aquifer in semi-arid India using borehole logs: implications for managed aquifer recharge - M. Alazard; A. Boisson; J-C. Maréchal; J. Perrin; B. Dewandel; T. Schwarz; M. Pettenati; G. Picot-Colbeaux; W. Kloppman; S. Ahmed (Hydrogeology Journal, 2016)

Dependence of model-based extreme flood estimation on the calibration period: case study of the Kamp River (Austria) - P. Brigode; E. Paquet; P. Bernardara; J. Gailhard; F. Garavaglia; P. Ribstein; F. Bourgin; C. Perrin; V. Andréassian (Hydrological Sciences Journal, 2015)

Hydrology under change: an evaluation protocol to investigate how hydrological models deal with changing catchments - G. Thirel; V. Andréassian; C. Perrin; J.-N. Audouy; L. Berthet; P. Edwards; N. Folton; C. Furusho; A. Kuentz; J. Lerat; G. Lindström; E. Martin; et al. (Hydrological Sciences Journal, 2015)

Determining the vertical evolution of hydrodynamic parameters in weathered and fractured south Indian crystalline-rock aquifers: insights from a study on an instrumented site - A. Boisson; N. Guihéneuf; J. Perrin; O. Bour; B. Dewandel; A. Dausse; M. Viossanges; S. Ahmed; J. C. Maréchal (Hydrogeology Journal, 2015)

Does calculating impair postural stabilization allowed by visual cues? - Hadrien Ceyte; Alexis Lion; Sébastien Caudron; Badreddine Kriem; Philippe P. Perrin; Gérome C. Gauchard (Experimental Brain Research, 2014)

Resurrection of Mesoplodon hotaula Deraniyagala 1963: A new species of beaked whale in the tropical Indo‐Pacific - Merel L. Dalebout; C. Scott Baker; Debbie Steel; Kirsten Thompson; Kelly M. Robertson; Susan J. Chivers; William F. Perrin; Manori Goonatilake; R. Charles Anderson; James G. Mead; Charles W. Potter; Lisa Thompson; et al. (Marine Mammal Science, 2014)
We present genetic and morphological evidence supporting the recognition of a previously synonymized species of Mesoplodon beaked whale in the tropical Indo‐Pacific, Mesoplodon hotaula . Although the new species is closely‐related to the rare ginkgo‐toothed beaked whale M. ginkgodens, we show that these two lineages can be differentiated by maternally (mitochondrial DNA ), biparentally (autosomal), and paternally (Y chromosome) inherited DNA sequences, as well as by morphological features. The reciprocal monophyly of the mt DNA genealogies and the largely parapatric distribution of these lineages is consistent with reproductive isolation. The new lineage is currently known from at least seven specimens: Sri Lanka (1), Gilbert Islands, Republic of Kiribati (1+), Palmyra Atoll, Northern Line Islands, U.S.A. (3), Maldives (1), and Seychelles (1). The type specimen (Sri Lanka) was described as a new species, M. hotaula , in 1963, but later synonymized with M. ginkgodens . This discovery brings the total number of Mesoplodon species to 15, making it, by far, the most speciose yet least known genus of cetaceans.

Climate‐driven range shifts explain the distribution of extant gene pools and predict future loss of unique lineages in a marine brown alga - J. Assis; E. A. Serrão; B. Claro; C. Perrin; G. A. Pearson (Molecular Ecology, 2014)
The climate‐driven dynamics of species ranges is a critical research question in evolutionary ecology. We ask whether present intraspecific diversity is determined by the imprint of past climate. This is an ongoing debate requiring interdisciplinary examination of population genetic pools and persistence patterns across global ranges. Previously, contrasting inferences and predictions have resulted from distinct genomic coverage and/or geographical information. We aim to describe and explain the causes of geographical contrasts in genetic diversity and their consequences for the future baseline of the global genetic pool, by comparing present geographical distribution of genetic diversity and differentiation with predictive species distribution modelling ( SDM ) during past extremes, present time and future climate scenarios for a brown alga, F ucus vesiculosus . SDM showed that both atmospheric and oceanic variables shape the global distribution of intertidal species, revealing regions of persistence, extinction and expansion during glacial and postglacial periods. These explained the distribution and structure of present genetic diversity, consisting of differentiated genetic pools with maximal diversity in areas of long‐term persistence. Most of the present species range comprises postglacial expansion zones and, in contrast to highly dispersive marine organisms, expansions involved only local fronts, leaving distinct genetic pools at rear edges. Besides unravelling a complex phylogeographical history and showing congruence between genetic diversity and persistent distribution zones, supporting the hypothesis of niche conservatism, range shifts and loss of unique genetic diversity at the rear edge were predicted for future climate scenarios, impoverishing the global gene pool.

Development of a new standardised method for sustainable monitoring of the vulnerable pink sea fan Eunicella verrucosa - R. Coz; V. Ouisse; C. Artero; A. Carpentier; A. Crave; E. Feunteun; J.-M. Olivier; B. Perrin; F. Ysnel (Marine Biology, 2012)

Characterization of the desiccation of wheat kernels by multivariate imaging - B. Jaillais; E. Perrin; C. Mangavel; D. Bertrand (Planta, 2011)

Heterozygosity–fitness correlations among wild populations of European tree frog ( Hyla arborea ) detect fixation load - E. LUQUET; P. DAVID; J.‐P. LENA; P. JOLY; L. KONECNY; C. DUFRESNES; N. PERRIN; S. PLENET (Molecular Ecology, 2011)
Quantifying the impacts of inbreeding and genetic drift on fitness traits in fragmented populations is becoming a major goal in conservation biology. Such impacts occur at different levels and involve different sets of loci. Genetic drift randomly fixes slightly deleterious alleles leading to different fixation load among populations. By contrast, inbreeding depression arises from highly deleterious alleles in segregation within a population and creates variation among individuals. A popular approach is to measure correlations between molecular variation and phenotypic performances. This approach has been mainly used at the individual level to detect inbreeding depression within populations and sometimes at the population level but without consideration about the genetic processes measured. For the first time, we used in this study a molecular approach considering both the interpopulation and intrapopulation level to discriminate the relative importance of inbreeding depression vs. fixation load in isolated and non‐fragmented populations of European tree frog ( Hyla arborea ), complemented with interpopulational crosses. We demonstrated that the positive correlations observed between genetic heterozygosity and larval performances on merged data were mainly caused by co‐variations in genetic diversity and fixation load among populations rather than by inbreeding depression and segregating deleterious alleles within populations. Such a method is highly relevant in a conservation perspective because, depending on how populations lose fitness (inbreeding vs. fixation load), specific management actions may be designed to improve the persistence of populations.

Ten polymorphic microsatellite markers for the endangered Australian Eastern Bristlebird, Dasyornis brachypterus - C. Perrin; D. G. Roberts (Conservation Genetics Resources, 2010)

Guidelines for the treatment of marine mammals in field research - N. J. Gales; W. D. Bowen; D. W. Johnston; K. M. Kovacs; C. L. Littnan; W. F. Perrin; J. E. Reynolds; P. M. Thompson (Marine Mammal Science, 2009)

Does life history predict past and current connectivity for rocky intertidal invertebrates across a marine biogeographic barrier? - D. J. AYRE; T. E. MINCHINTON; C. PERRIN (Molecular Ecology, 2009)
The southeast Australian coast potentially includes a complex biogeographic barrier, largely lacking exposed rocky shore that may limit the dispersal of rocky intertidal taxa and contribute to the maintenance of two biogeographic regions. Surprisingly, within the 300‐km barrier region, several species considered exposed rocky shore specialists occurred within sheltered sites. We analysed COI sequence variation for 10 rocky intertidal invertebrate species, with a range of life histories, to test the hypotheses that larval type and habitat specificity are strong predictors of gene flow between biogeographic regions. Our data revealed that the southeast corner of Australia includes a strong barrier to gene flow for six of eight species with planktonic larvae, and a coalescence analysis of sequence differentiation (IM model) suggests that a barrier has existed since the Pleistocene. In contrast, two direct developers were not affected by the barrier. Our comparative approach and data from earlier studies (reviewed here) do not support the hypothesis that larval type predicts gene flow across this barrier, instead we found that the ability to utilize sheltered habitat provides a clearer explanation of the phylogeographic break. Indeed, the species that displayed little or no evidence of a phylogeographic break across the barrier each displayed unexpectedly relaxed habitat specificity.

Effect of Chronic and Subchronic Organic Solvents Exposure on Balance Control of Workers in Plant Manufacturing Adhesive Materials - Guillaume Herpin; Imed Gargouri; Gérome C. Gauchard; Catherine Nisse; Moncef Khadhraoui; Boubaker Elleuch; Denis Zmirou-Navier; Philippe P. Perrin (Neurotoxicity Research, 2009)

Impaired neuromotor functions in hospital laboratory workers exposed to low levels of organic solvents - Guillaume Herpin; Gérome C. Gauchard; Alexandre Vouriot; Bernard Hannhart; Alain Barot; Jean-Marie Mur; Denis Zmirou-Navier; Philippe P. Perrin (Neurotoxicity Research, 2008)

A DIVERGENT mtDNA LINEAGE AMONG MESOPLODON BEAKED WHALES: MOLECULAR EVIDENCE FOR A NEW SPECIES IN THE TROPICAL PACIFIC? - Merel L. Dalebout; C. Scott Baker; Debbie Steel; Kelly M. Robertson; Susan J. Chivers; William F. Perrin; James G. Mead; Roger V. Grace; T. David Schofield (Marine Mammal Science, 2007)

Topographic shading and wave exposure influence morphology and ecophysiology of Ecklonia radiata (C. Agardh 1817) in Fiordland, New Zealand - S. R. Wing; J. J. Leichter; C. Perrin; S. M. Rutger; M. H. Bowman; C. D. Cornelisen (Limnology and Oceanography, 2007)
Patterns in morphology, pigment concentration, and light saturation kinetics of Ecklonia radiata reveal great morphological and physiological variability among individuals from sites spanning strong gradients in topographic shading and wave exposure among the 14 fjords in southwestern New Zealand. Morphology of E. radiata varies from relatively narrow (85 ± 4.7 mm) (mean ± standard error), thick (3.2 ± 0.30 mm) blades from the well‐illuminated, wave‐exposed outer coast sites to wide, undulate (460 ± 36.8 mm,) and thin (0.46 ± 0.059 mm) blades from quiescent, topographically shaded inner fjord sites. Chlorophyll a (Chl a ) concentration of blades (0.084‐1.34 µg g −1 of tissue) and the ratio of fucoxanthin to Chl a (0.33 to 0.56) also increased along this gradient, indicating photoacclimation within the inner fjord populations. In situ measurements of light saturation kinetics indicate maximum photosynthetic rates at lower irradiance (I max = 43.7 vs. 257 µmol quanta m −2 s −1 ) for algae at inner fjord sites relative to well‐lit outer fjord locations. Individuals exhibiting characteristically photoacclimated relative electron transfer rate curves had more deplete δ 13 C (‐13.35% to ‐22.35%) than individuals with higher I max . There was no significant association between the kelp morphology or geographic location and the observed recombinant DNA diversity of ITS sequences that would indicate the presence of two Ecklonia species in the fjords. E. radiata occupies a wide range of habitats in Fiordland and displays variability in morphology and photo‐physiological responses to low light that coincide with gradients in wave exposure and topographically shaded light conditions.

Optimizing carbon sequestration in commercial forests by integrating carbon management objectives in wood supply modeling - Charles P.-A. Bourque; Eric T. Neilson; Chris Gruenwald; Samantha F. Perrin; Jason C. Hiltz; Yvon A. Blin; Geoffrey V. Horsman; Matthew S. Parker; Christie B. Thorburn; Michael M. Corey; Fan-rui Meng; D. Edwin Swift (Mitigation and Adaptation Strategies for Global Change, 2007)

Contributions of occupational hazards and human factors in occupational injuries and their associations with job, age and type of injuries in railway workers - Nearkasen Chau; Gerome C. Gauchard; Dominique Dehaene; Lahoucine Benamghar; Christian Touron; Philippe P. Perrin; Jean-Marie Mur (International Archives of Occupational and Environmental Health, 2007)

Release of secondary free radicals during post-ischaemic reperfusion is not influenced by extracellular calcium levels in isolated rat hearts - C. Perrin-Sarrado; O. Bouchot; C. Vergely; L. Rochette (Molecular and Cellular Biochemistry, 2007)

Long-term exposure to solvents impairs vigilance and postural control in serigraphy workers - Alexandre Vouriot; Bernard Hannhart; Gérome C. Gauchard; Alain Barot; Torbjorn Ledin; Jean-Marie Mur; Philippe P. Perrin (International Archives of Occupational and Environmental Health, 2005)

Molecular Line Parameters for the “MASTER” (Millimeter Wave Acquisitions for Stratosphere/Troposphere Exchange Research) Database - A. Perrin; C. Puzzarini; J.-M. Colmont; C. Verdes; G. Wlodarczak; G. Cazzoli; S. Buehler; J.-M. Flaud; J. Demaison (Journal of Atmospheric Chemistry, 2005)

Relationships of job, age, and life conditions with the causes and severity of occupational injuries in construction workers - Nearkasen Chau; Grome C. Gauchard; Christian Siegfried; Lahoucine Benamghar; Jean-Louis Dangelzer; Martine Franais; Rgis Jacquin; Alain Sourdot; Philippe P. Perrin; Jean-Marie Mur (International Archives of Occupational and Environmental Health, 2004)

Reliability and validity of the Biodex system 3 pro isokinetic dynamometer velocity, torque and position measurements - Tamara C. Valovich-mcLeod; Sandra J. Shultz; Bruce M. Gansneder; David H. Perrin; Joshua M. Drouin (European Journal of Applied Physiology, 2004)

Compositional heterogeneity and microstructural diversity of coral skeletons: implications for taxonomy and control on early diagenesis - C. Perrin (Coral Reefs, 2003)

The neuronal targets for GABAergic reticulospinal inhibition that stops swimming in hatchling frog tadpoles - W.-C. Li; R. Perrins; A. Walford; A. Roberts (Journal of Comparative Physiology A, 2003)

Renal handling of salt and water in humans during exercise with or without hydration - J-P. Mallié; Z. Ait-Djafer; C. Saunders; A. Pierrat; M. Caira; O. Courroy; V. Panescu; P. Perrin (European Journal of Applied Physiology, 2002)

Mitochondrial DNA analysis of the geographic structure of Indian scad mackerel in the Indo‐Malay archipelago - C. Perrin; P. Borsa (Journal of Fish Biology, 2001)
Sequence analysis of a fragment of the cytochrome b gene in Decapterus russelli sampled from the Indo‐Malay archipelago revealed two distinct mitochondrial clades (mean nucleotide divergence=2·2%) whose geographic distribution was heterogeneous (Nei's G ST =0·416). This pointed to a complex pattern of genetic differentiation and demonstrated limited genetic exchange between populations in this highly mobile species.

Rapid and efficient identification of microsatellite loci from the sea urchin, Evechinus chloroticus - C. Perrin; M. S. Roy (Molecular Ecology, 2000)

Rapid and efficient identification of microsatellite loci from the sea urchin, Evechinus chloroticus - C. Perrin; M. S. Roy (Molecular Ecology, 2000)

Monsoonal influences on a mesoscale convective systemover midlatitude South Australia - G. M. Perrin; C. J. C. Reason (Meteorology and Atmospheric Physics, 2000)

Acoustical recognition of laryngeal pathology: a comparison of two strategies based on sets of features - E. Perrin; C. Berger-Vachon; L. Collet (Medical & Biological Engineering & Computing, 1999)

The effects of increasing CO 2 and temperature on oak leaf palatability and the implications for herbivorous insects - S. J. Dury; J. E. G. Good; C. M. Perrins; A. Buse; T. Kaye (Global Change Biology, 1998)
Rising levels of atmospheric CO 2 are expected to perturb forest ecosystems, although the extent to which specific ecological interactions will be modified is unclear. This research evaluates the effects of elevated CO 2 and temperature, alone and in combination, on the leaf nutritional quality of Pendunculate oak ( Quercus robur L. ), and the implications for herbiverous insect defoliators are discussed. A 3 °C temperature rise reduced leaf nutritional quality, by reducing foliar nitrogen concentration and increasing condensed tannin content. Doubling atmospheric CO 2 temporarily increased total phenolics, but also reduced leaf toughness. The nutritional quality of the second leaf flush (lammas growth) was considerably reduced at elevated CO 2 . It is concluded that larval development of spring‐feeding defoliators and hence adult fecundity may be adversely affected by increased temperatures.

Solarization in a forest nursery: effect on ectomycorrhizal soil infectivity and soil receptiveness to inoculation with Laccaria bicolor - M. L. Soulas; B. L. Bihan; P. Camporota; C. Jarosz; M. I. Salerno; R. Perrin (Mycorrhiza, 1997)

Acoustical recognition of laryngeal pathology using the fundamental frequency and the first three formants of vowels - E Perrin; C. Berger-Vachon; I. Kauffmann; L. Collet (Medical & Biological Engineering & Computing, 1997)

A new immunostimulatory complex (PICKCa) in experimental rabies: antiviral and adjuvant effects - H. X. Lin; C. Gontier; M-F. Saron; P. Perrin (Archives of Virology, 1993)